2000
DOI: 10.1144/jgs.157.6.1155
|View full text |Cite
|
Sign up to set email alerts
|

A structural model for the western-central Sudetes: a deformed stack of Variscan thrust sheets

Abstract: A model based on new structural and geochemical data is presented. It unifies the structural history of the Izera, Rudawy Janowickie and Kaczawa complexes with the Fore Sudetic block, despite their current separation by the Intra-Sudetic and Marginal Sudetic faults. Above the granitoid Izera, Kowary and Wa¸droże gneisses, at the base of the structural sequence, the ductile Kowary shear zone marks the basal decollement of the Świerzawa thrust sheet, comprising often highly strained metasediments assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 22 publications
2
51
0
1
Order By: Relevance
“…Avalonia: Is, Istanbul; Mg, Meguma; Mo, Moesia; sP, south Portuguese; Zo, Zonguldak. (Dean et al, 2000, proposed an Avalonian origin for the Istanbul Paleozoic; see also Seston et al, 2000, andWinchester, 2002). Cadomia: AA, Austro-Alpine; Cm, Cadomia; He, Helvetic; Ib, allochthons from northwestern Iberia; Lg, Ligerian; MD, Moldanubian; Pe, Penninic; SM, Serbo-Macedonian; Sx, Saxo-Thuringian.…”
Section: P R O T O T E T H Y S a S I A T I C T A C O N Ic A R C T A Cmentioning
confidence: 99%
“…Avalonia: Is, Istanbul; Mg, Meguma; Mo, Moesia; sP, south Portuguese; Zo, Zonguldak. (Dean et al, 2000, proposed an Avalonian origin for the Istanbul Paleozoic; see also Seston et al, 2000, andWinchester, 2002). Cadomia: AA, Austro-Alpine; Cm, Cadomia; He, Helvetic; Ib, allochthons from northwestern Iberia; Lg, Ligerian; MD, Moldanubian; Pe, Penninic; SM, Serbo-Macedonian; Sx, Saxo-Thuringian.…”
Section: P R O T O T E T H Y S a S I A T I C T A C O N Ic A R C T A Cmentioning
confidence: 99%
“…In this event the orogenic wedge in the West Sudetes generally propagated from east to west. In the Karkonosze-Izera complex (central West Sudetes) this is shown by: a) early kinematic indicators in mylonitic ductile shear zones (Mazur 1995;Seston et al 2000); b) the decrease in metamorphic grade from garnet zone in the east to chlorite zone in the NW (Baranowski et al 1990;Kachlfk & Pato~ka 1998;Collins et al 2000); c) the decrease of 41)Ar-39Ar cooling ages towards the west (Marheine et al 1999); d) diminishing ages of flysch sedimentation onsets towards the west showing that tectonic exhumation was much earlier in the east. In addition, pre-late Devonian unconformities occur in the central West Sudetes between the Ktodzko metamorphic complex and the Bardo Unit (Hladil et al 1998;Kryza et al 2000), while late Devonian coarsegrained clastic sedimentary fills derived from exhumed metamorphic complexes to the east were deposited in syntectonic basins (Aleksandrowski & Mazur 2002).…”
Section: Avaloniamentioning
confidence: 99%
“…Oliver et al 1993;KrOner & Hegner 1998). Others suggested that the absence of supporting geological evidence for an arc edifice at the time makes it more likely that chemical characteristics of the intrusions were inherited from extensive melting of the calc-alkaline Cadomian basement (Kryza & Pin 1997;Aleksandrowski et al 2000: Floyd et al 2000. Subsequent dominantly basic magmatism was associated with clastic basin-fill metasedimentary rocks, typical of magmatism associated with an extensional tectonic setting.…”
Section: Avaloniamentioning
confidence: 99%
See 2 more Smart Citations